PARTISIPASI PEREMPUAN DALAM MUSYAWARAH PERENCANAAN PEMBANGUNAN (MUSRENBANG) DI KAMPUNG NOTOHARJO KECAMATAN TRIMURJO KABUPATEN LAMPUNG TENGAH - Mirnawati; Wahyu Widodo; Sigit Setioko (Yayasan Nusantara Hasana Berdikari, 2023)
Community activities, especially women in Notoharjo Village, Trimurjo District, Central Lampung Regency, in the Village Development Planning Deliberation (Musrenbang) are still low. The control of women in Noto Harjo Village, Trimurjo District in Musrenbang is still low. The benefits of Musrenbang for women are still not able to reach women's interests such as increasing education and training for women through Family Welfare Empowerment (PKK). Based on the description of the background above, the problem formulated is: How is the participation of women in the Development Planning Deliberation (Musrenbang) in Notoharjo Village, Trimurjo District, Central Lampung Regency? In this study, the data collection methods used were interviews, observation and documentation. The data analysis technique used is a qualitative technique. Based on the results of research in the field, it can be concluded as follows: 1). The participation of women's thoughts in the Musrenbang process is carried out through women's representatives represented by the head of the PKK Mobilization Team, Chair of the Women Farmers Group and Posyandu Cadre, women actively participate in contributing their thoughts in the form of ideas and receive Appreciation from the Notoharjo Village Government, Trimurjo District, and poured into the APBK of Kampung Notoharjo and realized into the APBK of Kampung Notoharjo. 2). There is the participation of women workers in the Musrenbang of Kampung Notoharjo in activities to help prepare for consumption, as well as helping to tidy up the village hall before and after the Musrenbang event. 3). There is participation of women who have skills through ideas given through their representatives, because not all women who have skills are invited to the Musrenbang of Notoharjo Village to adjust the budget of Musrenbang participants according to what is listed in the APBK of Notoharjo Village, Trimurjo District 4). There was no participation of women's goods in the Musrenbang of Kampung Notoharjo because the facilities and infrastructure at the Notoharjo Village Hall were complete. 5). There is no women's money participation in the Musrenbang of Kampung Notoharjo, because the Musrenbang activities have been budgeted for in the APBK of Kampung Notoharjo.